Bladder perforation by orthopedic implants 26 years after limb-sparing surgery for left proximal femoral chondrosarcoma: A case report. (2020) - Iwatsu, Jun; Watanuki, Munenori; Hayashi, Kouu; Yoshida, Shinichirou; Yano, Toshihisa; Hatori, Masahito; Hosaka, Masami; Hagiwara, Yoshihiro; Itoi, Eiji
Highlights: A patient underwent limb-sparing surgery for left proximal femoral chondrosarcoma. Bladder perforation by staples occurred 26 years after limb-sparing surgery. No reports describe staple migration into the bladder after limb-sparing surgery. Bladder injury is possible in patients with urinary symptoms after pelvic surgery. Implant complications may occur even after a long postoperative period. Abstract: Introduction: The need for implant use during orthopedic surgeries has been increasing. Accordingly, increased implant failures have been reported. However, bladder perforation remains a rare complication after orthopedic surgery. Although a few reports have described bladder perforation after total hip arthroplasty, no previous studies have reported the migration of staples into the bladder after limb-sparing surgery. Presentation of case: A 65-year-old patient underwent limb-sparing surgery to remove a chondrosarcoma in the left proximal thigh. Twenty-six years after surgery, a staple that had been used to fix artificial ligaments to the pubis migrated to perforate the bladder, resulting in painful urination. The staple was removed, and her symptoms improved. Discussion: In this case, bladder perforation by the staple resulted in painful urination. The bladder perforation was not detected until 26 years after the initial surgery. Conclusion: Our observations emphasize that implant complications may occur even after a long postoperative period, and the possibility of delayed bladder perforation from previous pelvic surgeries should be considered in patients presenting with urinary tract symptoms.